Social inclusion of young people from the most disadvantaged social strata of the population in their community and school - Ferreira Salles, Leila Maria [UNESP]; Iaman, A.; Eskicumali, A. (Elsevier B.V., 2015)
This paper analyses the social inclusion of young people from the most disadvantaged social strata of the population in a community, in Brazil. Focal interviews were conducted with two groups, protagonists and non protagonists of violence, in two public schools. The analysis indicates the two groups attend different places, have different expectations of leisure, and life activities are also differentiated. Young people not considered protagonists of violence believe in shape their own future and the importance of the school. The protagonists don't. For them, school is just for fun, not to conquer a better future. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: young people; school; violence